2018
DOI: 10.1016/j.energy.2018.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Application of Micro Gas Turbine in Range-Extended Electric Vehicles

Abstract: The increasing number of passenger cars worldwide and the consequent increasing rate of global oil consumption have raised the attention on fuel prices and have caused serious problems to the environment. Nowadays, the demand for reducing fuel consumption and pollutant emissions has paved the way to the development of more efficient power generation systems for the transportation sector. The lower fuel burning and pollutant emissions of hybrid electric vehicles give a strong motivation and encourage further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…Unlike Karvountzis-Kontakiotis et al [227] who found a 34% increase in energy consumption for a gas turbine range extender (for a light-duty vehicle) compared to a baseline diesel, the present study predicts a 20-65% improvement in energy consumption of the gas turbine drivetrain compared to the baseline diesel. The discrepancy is mainly due to the thermal efficiency assumptions: 30% [185] for a gas turbine in the present study, compared to 26% in Karvountzis-Kontakiotis et al [227] study. Different assumptions related to drive cycle and battery size are additional reasons for the discrepancy.…”
Section: Energy Consumption Resultscontrasting
confidence: 80%
“…Unlike Karvountzis-Kontakiotis et al [227] who found a 34% increase in energy consumption for a gas turbine range extender (for a light-duty vehicle) compared to a baseline diesel, the present study predicts a 20-65% improvement in energy consumption of the gas turbine drivetrain compared to the baseline diesel. The discrepancy is mainly due to the thermal efficiency assumptions: 30% [185] for a gas turbine in the present study, compared to 26% in Karvountzis-Kontakiotis et al [227] study. Different assumptions related to drive cycle and battery size are additional reasons for the discrepancy.…”
Section: Energy Consumption Resultscontrasting
confidence: 80%
“…Microturbines are a good alternative to ICE because it produces less gaseous emission such as HC and CO [44]. Additionally, it also weighs less than a similarsized ICE as it is possible to omit cooling and the oil circuit.…”
Section: Microturbinementioning
confidence: 99%
“…The effect of using EGR on the engine combustion and engine performance has been well studied by many of researchers over a wide range of all ICE types. In general, four major effects of utilizing EGR on combustion characteristics can be explained as follows [7,[36][37][38][39][40]: (1). Charge Heating Effect-The temperature of intake charge will be increased by hot-burned gases.…”
Section: Influence Of Egr Applicationmentioning
confidence: 99%